STRATEGI ALGORITMA DEPTH-FIRST SEARCH (DFS) DAN ALPA BETA PRUNING PADA PERMAINAN COC (Clash of Clans) - Budi Yanto; Erni Rouza; Jufri - (RJOCS (Riau Journal of Computer Science), 2017)
Game development is supported by the increasingly sophisticated Android technology that exists either in the model or operating system. Android is one of the most sophisticated mobile phone operating systems today. One of the most popular and artificial intelligence games game in the world, such as COC (Clash of Clans) is a Strategy game where players build community, train troops, and attack other players to get gold, trophy, elixir and dark elixir , Build defenses that protect players from other players' attacks, and to train and improve the ability and number of troops .The application of artificial intelligence algorithm with Negamax algorithm optimized with Alpha Beta Pruning can reduce the searchspace so that the evaluation process can be done more quickly.